FGF21 Is Released During Increased Lipogenesis State Following Rapid-Onset Radioiodine-Induced Hypothyroidism - Szczepańska, Ewa; Glinicki, Piotr; Zgliczyński, Wojciech; Słowińska-Srzednicka, Jadwiga; Jastrzębska, Helena; Gietka-Czernel, Małgorzata (Frontiers in Endocrinology, 2022)
Background FGF21 pharmacological treatment reverses fatty liver and lowers serum triglyceride concentration but FGF21 serum level is increased in hepatic steatosis. FGF21 secretion is induced by thyroid hormones in vitro. Purpose To determine the influence of thyroid hormones and metabolic changes secondary to thyroid dysfunction on FGF21 secretion in humans. Materials and Methods This was a case-control study. 82 hyperthyroid and 15 hypothyroid patients were recruited together with 25 healthy controls. Of those with hyperthyroidism, 56 received radioiodine treatment and 42 of them achieved hypothyroidism and then euthyroidism within one year following therapy. Radioiodine-induced hypothyroidism developed abruptly within a six week interval between clinic visits. FGF21 serum levels were determined with an ELISA method. Results Serum FGF21 levels did not differ in hyper- and hypothyroid patients in comparison to controls [median 103.25 (interquartile range, 60.90-189.48) and 86.10 (54.05-251.02) vs 85.20 (58.00-116.80) pg/mL P=0.200 and 0.503, respectively]. In hyperthyroid patients treated with radioiodine, serum FGF21 levels increased significantly in rapid-onset hypothyroidism in comparison to the hyperthyroid and euthyroid phase [median 160.55 (interquartile range, 92.48 - 259.35) vs 119.55 (67.78-192.32) and 104.43 (55.93-231.93) pg/mL, P=0.034 and 0.033, respectively]. The rising serum FGF21 level correlated positively with serum triglycerides (Spearman coefficient rs=0.36, P=0.017) and inversely with serum SHBG (rs=-0.41, P=0.007), but did not correlate with thyroid hormone levels. Conclusions There was a transient increase in FGF21 serum level during rapid-onset hypothyroidism following radioiodine treatment. There was no association between FGF21 serum level and thyroid hormones. In radioiodine-induced hypothyroidism, the rising serum FGF21 concentration correlated positively with rising serum triglycerides and negatively with falling SHBG, reflecting increased hepatic lipogenesis.